2007
DOI: 10.1080/10615800701303215
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and health problems in a geographically proximate population time-sampled continuously for three months after the September 11th, 2001 terrorist incidents

Abstract: This study assessed the mental and physical health status and psychological problems related to the September 11th terrorist incidents among a representative sample of adults living near New York City, using continuously time-sampled data collected throughout 2001. Prevalence estimates for poor mental or physical health after September 11th (October through December) were comparable to those for the entire year of 2001 (i.e. approximately 33%). Psychological problems related to the terrorist incidents were rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(23 citation statements)
references
References 54 publications
3
19
1
Order By: Relevance
“…First, the contractors were all men and older than the average soldier. Gender and age may influence PTSD, depression, and psychological distress scores (Bruce et al, 2001;Ford, Adams, & Dailey, 2007). Second, although contractors and soldiers may share an exposure to grave danger, the resources and support they are provided with to deal with these challenges differ considerably, as our study reveals.…”
Section: Discussionmentioning
confidence: 54%
“…First, the contractors were all men and older than the average soldier. Gender and age may influence PTSD, depression, and psychological distress scores (Bruce et al, 2001;Ford, Adams, & Dailey, 2007). Second, although contractors and soldiers may share an exposure to grave danger, the resources and support they are provided with to deal with these challenges differ considerably, as our study reveals.…”
Section: Discussionmentioning
confidence: 54%
“…A prospective study of residents of Connecticut, a state contiguous with New York City, found that although psychological problems related to the terrorist incidents were reported by more than half of the respondents, measures of overall physical or mental health did not change in the 3 months after September 11th (Ford, Adams, & Dailey, 2007). Some evidence has shown, however, physical signs of stress in remote populations.…”
Section: Distress and Pathologymentioning
confidence: 99%
“…A review of 160 catastrophes demonstrated more negative mental health responses following terrorist disasters than following natural or technical disasters (Norris, Friedman, & Watson, 2002). Emotional distress, anxiety and depressive symptoms are common reactions in populations directly affected by terrorist attacks (Chen, Chung, Chen, Fang, & Chen, 2003; Ford, Adams, & Dailey, 2007). In the three to five days after the attacks on 11 September 2001 in the US, 44% experienced substantial stress reactions, 90% experienced at least low levels of stress and 47% reported increased anxiety and fear (DiMaggio & Galea, 2006; Schuster et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Although the risk of being directly hit by such attacks is quite limited, the perception that anyone can be hit at any moment may engender feelings of threat. Rather than objective factors, such as proximity to the terrorist attack, the perception of threat has a psychological effect (Ford et al, 2007; Hansen, Nissen, & Heir, 2013; Nissen, Birkeland Nielsen, Solberg, Bang Hansen, & Heir, 2015). Although several studies have found an association between exposure and post-traumatic symptoms (Hansen et al, 2013; Heir, Blix, & Knatten, 2016), other studies did not find such association (Bleich et al, 2003; Ford et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation